Effect of ISBAR3 Training on Improving Communication among Nursing Team in Inpatient Unit of Pariaman Hospital - Husna, Novriani; Said, Faridah Binti Mohd; Nambiar, Nisha (International Journal of Multidisciplinary Approach Research and Science, 2025)
Nursing handover is a critical component in health services that requires accurate and appropriate communication to ensure patient safety. This study aims to analyze the effect of ISBAR3 (Identity, Situation, Background, Assessment, Recommendation, and Readback) training on improving the communication of the nursing team in the inpatient unit of Pariaman Hospital. Using quantitative methods with pre-test and post-test designs, the study involved 30 nurses as respondents. Data were collected through structured questionnaires, observations, and in-depth interviews. The results showed a significant increase in communication scores from 65% to 85% post-training. Statistical analysis confirmed the effectiveness of the intervention with a p < value of 0.05. The implementation of ISBAR3 contributed to a reduction in miscommunication incidents from 3.5 to 0.8 events per week and a 35% reduction in emergency response time. The increase in staff confidence in clinical communication was reflected in the rise in the score from 65.3 to 87.8. Despite the challenges of implementation, the development of a comprehensive mitigation strategy facilitates the continued adoption of the ISBAR3 method. The study concluded that ISBAR3 training was effective in improving the quality of communication of the nursing team with positive implications for patient safety and service efficiency.